Investigation of adenosine A1 receptor-mediated β-arrestin 2 recruitment using a split-luciferase assay - Saecker, Luisa; Häberlein, Hanns; Franken, Sebastian (Frontiers in Pharmacology, 2023)
Background: Adenosine A1 receptor (A1AR) plays a prominent role in neurological and cardiac diseases as well as during inflammatory processes. Its endogenous ligand adenosine is known to be one of the key players in the sleep-wake cycle. Like other G protein-coupled receptors, stimulation of A1AR leads to the recruitment of arrestins in addition to the activation of G proteins. So far, little is known about the role of these proteins for signal transduction and regulation of A1AR compared to the activation of G proteins. In this work, we characterized a live cell assay for the A1AR mediated β-arrestin 2 recruitment. We have applied this assay to a set of different compounds that interact with this receptor. Methods: Based on NanoBit® technology, a protein complementation assay was developed in which the A1AR is coupled to the large part of the nanoluciferase (LgBiT) whereas its small part (SmBiT) is fused to the N-terminus of β-arrestin 2. Stimulation of A1AR results in the recruitment of β-arrestin 2 and subsequent complementation of a functional nanoluciferase. For comparison, corresponding data on the effect of receptor stimulation on intracellular cAMP levels were collected for some data sets using the GloSensor™ assay. Results: The assay gives highly reproducible results with a very good signal to noise ratio. Capadenoson, in contrast to adenosine, CPA or NECA, shows only partial agonism in this assay with respect to the recruitment of β-arrestin 2, whereas it is a full agonist in the case of the inhibitory effect of A1AR on cAMP production. By using a GRK2 inhibitor, it becomes clear that the recruitment is at least partially dependent on the phosphorylation of the receptor by this kinase. Interestingly, this was also the first time that we were able to demonstrate the A1AR mediated recruitment of β-arrestin 2 by stimulation with a valerian extract. Conclusion: The presented assay is a useful tool for the quantitative study of the A1AR mediated β-arrestin 2 recruitment. It allows data collection for stimulatory, inhibitory as well as modulatory substances and is also suitable for more complex substance mixtures such as valerian extract.